Job Satisfaction Mediates Improved Employee Performance: Contribution of Organizational Commitment and Organizational Culture - Qomariah Lahamid; Miranda Putri; Nurlasera Nurlasera (Equity: Jurnal Ekonomi, 2024)
This research was conducted at PT. Tasma Puja Sei Kuamang Kampa. The purpose of this research is to determine the influence of organizational commitment and organizational culture on employee performance which is mediated by job satisfaction at PT. Tasma Puja Sei Kuamang Kampa. The sampling method in this research is based on Gpower. The number of samples used was 99 employees. The data used is primary data and secondary data, the quantitative data analysis method uses the Smart PLS4 analysis technique. The research results show that organizational culture has a significant effect on job satisfaction and employee performance. However, organizational commitment has no effect on employee job satisfaction and employee performance. Interestingly, organizational commitment and organizational culture have a significant effect on employee performance and are mediated by employee job satisfaction at PT. Tasma Puja Sei Kuamang Kampa was 68.6%. The remaining 31.4% are variables not examined in this study.